2012
DOI: 10.1213/ane.0b013e31824e5bc4
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Desaturation After Propofol/Remifentanil-Induced Apnea

Abstract: Administered with propofol 2 mg/kg, the remifentanil dose necessary to produce acceptable intubating conditions, 2 mcg/kg, produces apnea that carries a significant risk of desaturation, whereas a remifentanil dose of 1.5 mcg/kg does not reliably produce acceptable intubating conditions and does not eliminate the risk of desaturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Combining propofol with remifentanil, 1.0 to 4.0 μg·kg -1 provided acceptable intubating conditions [1,2,4,17]. Remifentanil 2 μg·kg -1 and propofol 2.0 mg·kg -1 were sufficient to obtain excellent intubating conditions in 11 of 12 healthy volunteers [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining propofol with remifentanil, 1.0 to 4.0 μg·kg -1 provided acceptable intubating conditions [1,2,4,17]. Remifentanil 2 μg·kg -1 and propofol 2.0 mg·kg -1 were sufficient to obtain excellent intubating conditions in 11 of 12 healthy volunteers [17].…”
Section: Discussionmentioning
confidence: 99%
“…Remifentanil 2 μg·kg -1 and propofol 2.0 mg·kg -1 were sufficient to obtain excellent intubating conditions in 11 of 12 healthy volunteers [17]. The drugs were given over 5 to 10 seconds, the propofol immediately after the remifentanil, a method which is safe in healthy volunteers or young patients, but not for patients of ASA grade II or III.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These registries allow insights into not only individual and group performance but also infrequent outcomes such as failed intubations and rescue intubations. Although rescue intubation is deemed to be important [ 3 , 30 - 32 ], previous studies in the ED setting only examined the characteristics of rescue intubations and the predictors for successful rescue attempts after one failed attempt (i.e., not after multiple failed intubation attempts) [ 8 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, it may be preferred over succinylcholine in compromised patients in whom hemodynamic or other changes are to be minimized. A dose of rocuronium usually used for Rapid Sequence Induction (RSI) 1mg/kg, allows rapid paralysis (60 to 90 seconds) but the duration of action is prolonged (35-75 minutes), making it unsuitable in difficult airway scenarios in the unavailability of sugammadex 6 . One study by Sørensen M et al 7 has shown that with rocuronium, 93% of cases had excellent intubation, while with succinylcholine, 76% of cases had excellent intubation.…”
Section: Introductionmentioning
confidence: 99%